Cover Feature: Lignin–Inorganic Interfaces: Chemistry and Applications from Adsorbents to Catalysts and Energy Storage Materials (ChemSusChem 17/2020). Issue 17 (10th August 2020) - Budnyak, Tetyana M.; Slabon, Adam; Sipponen, Mika H.
Abstract : The Cover Feature shows lignin–inorganic hybrid and composite materials as an emerging type of materials with soft/hard interface and attractive properties to applications such as adsorption, catalysis, and energy storage. The cover artwork was proposed and designed by Jinrong Liu. More information can be found in the Minireview by T. M. Budnyak et al .